Investigating the Factors Affecting the Electronic Well-Being of Female Customers on Purchasing from Electronic Brand Store during pandemic crises - Yazdan Shirmohammadi; Morad Baradarn; Esmail Nasiri; amene kamali sarvestani (فصلنامه زن و جامعه)
Introduction: This research aims to study the factors on women's electronic health and the intention to use it regularly Methodology: This research is descriptive-survey in terms of practical purpose and data collection method. In the process of conducting this research, Digikala online store was investigated and 384 female customers of this store were selected as a statistical sample using the available sampling method from the unlimited population. Using the questionnaire and SPSS 23 and AMOS 23 software, data analysis was done.Findings: The findings showed that all the investigated factors (effect of performance expectation, effort expectation, and social influence, facilitation of conditions, hedonic motivation, price value, habit, online review, online follow-up, and online rating) have a positive and significant effect on electronic well-being. Their intention to continuously use Digikala online store products is another category that has been influenced by these factorsDiscussion and Conclusion: The results indicate that in the virtual world affected by the corona virus, the concept of "electronic welfare of female citizens" has become a necessity, and in such conditions, providing electronic services to female citizens is not only a choice, but a requirement.